Superficial protection of concrete with epoxy resin impregnations: influence of the substrate roughness and moisture - Rodrigues, M. P. (2014)
Submitted by Mario Pereira (majo@lnec.pt) on 2014-12-15T17:11:19Z No. of bitstreams: 1 Materials and Structures.pdf: 4695587 bytes, checksum: 9eee1de037f108d2a55e80cbefcc4843 (MD5)